(untitled) (JURNAL GEOGRAFI, 2025)
Indonesians must have high literacy to know about the disasters around them. There needs to be a learning model to improve disaster literacy. One of the alternatives is the Problem-based learning model with Root Cause Analysis. This research is a quantitative type of pseudo experiment with a pretest-posttest control group design where the pretest-posttest results of the experimental class and control class are compared to determine the effectiveness of the treatment in the experimental class. There are no particular specifications regarding the characteristics of the class used in the study. Data analysis used a sample t-test supported by prerequisite tests such as homogeneity and normality tests. The PBLRCA model has a significant effect on students’ disaster literacy skills. The results showed increased literacy skills at a t value of 5,787. Steps such as independent review, investigating the root of the problem, and implementing action plans that can make PBLRCA students read, explore and analyze situations in depth more than Lecturing Method. These activities make students’ disaster literacy improve.